Enzymes inhibitory property, antioxidant activity and phenolics profile of raw and roasted red sorghum grains in vitro - Irondi, E.A.; Adegoke, B.M.; Effion, E.S.; Oyewo, S.O.; Alamu, Emmanuel Oladeji; Boligon, A.A. (Elsevier, 2019)
Whole grain cereals are important dietary sources for management of metabolic diseases due to the bioactive components they contain. Hence, this study investigated enzymes (pancreatic lipase, α-amylase, α-glucosidase, xanthine oxidase and angiotensin 1-converting enzyme) inhibitory property, antioxidant activity and phenolics profile of raw and roasted red sorghum (Sorghum bicolor) grains in vitro. Extracts of flours of raw and roasted (150 °C and 180 °C, for 20 min) grains were assayed for enzymes inhibitory and antioxidant activities using spectrophotometric methods; while their phenolic constituents were characterized using HPLC-DAD. The raw grains exhibited strong enzymes inhibitory and antioxidant activities, and contained phenolic acids (gallic, chlorogenic, caffeic, ellagic and p-coumaric acids) and flavonoids (quercetin, luteolin and apigenin). However, whereas the enzymes inhibitory activity and levels of the phenolic compounds in the grains decreased significantly (p < 0.05) with increasing roasting temperature, the antioxidant activity increased. Hence, roasting at high temperature may not be recommended for the optimum retention of the enzymes inhibitory property and phenolic compounds of red sorghum grains.